PW 0395 Injury impacts all survey: a cross-sectional review of the injury prevention workforce in western australia. (November 2018) - Wold, Catrina; Jancey, Jonine; Crawford, Gemma; Hallett, Jonathan; Leavy, Justine; Hunt, Kristen; Smith, Christine; Sweeney, Roisin; Milner, Russ
Abstract : In 2012 in Western Australia (WA), preventable injuries were responsible for over 1000 deaths, 50 000 hospitalisations and more than 1 70 000 emergency department visits, with financial implications costing the community and healthcare system over nine billion dollars. The injury prevention and safety promotion workforce raises awareness of prevention strategies and implements programs and policies to increase community safety. To our knowledge, no state-wide assessment to establish the scope of the injury prevention and safety promotion workforce is currently available. The objective was to develop and implement a survey instrument to assess who is working in injury prevention, what type of work is being completed, and establish how the workforce needs to be supported in WA. A cross-sectional survey to assess the scope of the workforce was undertaken with a sample of injury prevention professionals (n=230) across WA. The sample consisted of people and organisations based in WA and who met one of the following criteria: 1) Engaged with the Know Injury program; 2) Their purpose aligned with the definition of injury; and/or 3) Were identified by an expert panel to work within the scope of injury prevention. The survey instrument was developed using previously validated question items and distributed via a web-based survey platform over a four-week period. Analysis consisted of descriptives, univariate and bivariate analysis and qualitative responses were analysed thematically. Ethical approval was granted through the Human Research Ethics Committee at Curtin University [RDHS-70–15]. There is now an effective survey instrument to understand the scope of the injury prevention workforce. The findings reflect who is working in injury prevention, the type of work being undertaken and how the workforce can be supported. With this information, the workforce will be able to better direct resources, increase engagement, continue improvement to programs, focus advocacy work and guide future initiatives.